2020
DOI: 10.1002/ardp.202000225
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, anticonvulsant, and antinociceptive activity of new 3‐(3‐methyl‐2,5‐dioxo‐3‐phenylpyrrolidin‐1‐yl)propanamides and 3‐phenyl‐butanamides

Abstract: A focused library of new 3‐(3‐methyl‐2,5‐dioxo‐3‐phenylpyrrolidin‐1‐yl)propanamides and their nonimide analogs were synthesized and tested for anticonvulsant activity. These compounds were obtained through the coupling reaction of the starting carboxylic acids with appropriate amines. The initial anticonvulsant screening was performed in mice (intraperitoneal administration) using the maximal electroshock seizure (MES) and the subcutaneous pentylenetetrazole (scPTZ) seizure models. The most promising compound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Later, Obniska et al [ 59 ] expanded the same class of pyrrolidine-2,5-diones by substituting the thiophene ring with an unsubstituted phenyl moiety. The new compounds 66a–m (Fig.…”
Section: Pyrrolidine Derivatives Obtained By Ring Synthesismentioning
confidence: 99%
“…Later, Obniska et al [ 59 ] expanded the same class of pyrrolidine-2,5-diones by substituting the thiophene ring with an unsubstituted phenyl moiety. The new compounds 66a–m (Fig.…”
Section: Pyrrolidine Derivatives Obtained By Ring Synthesismentioning
confidence: 99%
“…It is known that disubstituted piperazines can exhibit a wide range of pharmacological activity; they can act as anticonvulsant, 17 antifungal, 18 antiviral, 19 radioprotective, 20 antibacterial and antimalarial 21,22 agents. Accordingly, our studies in this field have shown that piperazine derivatives of pyrano [3,4-c]pyridines display high antibacterial 23 and neurotropic activity.…”
Section: Introductionmentioning
confidence: 99%